How Bedfordshire voted, 1685-1735 : the evidence of local poll books. - Collett-White, James (Publications of the Bedfordshire Historical Record Society., 2008)
This second volume of BHRS's series of late seventeenth and early eighteenth-century poll books continues the story of Bedfordshire voting in the context of local and national politics up to the election in 1734. It contains transcriptions of the poll books for four Bedford borough elections and three county elections held between 1722 and 1734. Except for the 1722 county election, the poll books are taken from hitherto unpublished manuscripts. Much of the political and local background to voting is recounted in Volume 1. For this volume, each chapter has an introduction which draws upon letters to provide an insight into the political alliances and manoeuvres which occurred in selecting candidates, including the part played by the Duchess of Marlborough. The poll books themselves are a mine of local information about Bedfordshire. The 10,000 names in this volume (fully indexed), added to the 8,500 names in the first volume, provide evidence for in-depth study of people, places and landholding in Bedfordshire. They will also help family historians find ancestors between the 1671 Hearth Tax and the 1841 Census.